Intrascrotal Abscess, Propionibacterium acnes and Staphylococcus cohnii ssp. cohnii: A Case Report and Review of the Literature - Masciovecchio Stefano; Alessandro Del Rosso; Pietro Saldutto; Giuseppe Paradiso Galatioto; Carlo Vicentini (Case Reports in Urology)
Introduction. The Propionibacterium acnes and the Staphylococcus cohnii ssp. cohnii are occasional pathogenic bacteria. The intrascrotal localization of the Propionibacterium acnes is exceptional. The Staphylococcus cohnii ssp. cohnii is not able to colonize the urogenital apparatus but it is the most frequently responsible for blood culture contamination even if it can sustain, in particular conditions, systemic infections. Case Presentation. We report the case of a 72-year-old man who is under observation for pain and swelling of the left hemiscrotum associated to high fever. The scrotal ultrasound shows the presence of a left intra-scrotal abscess with didymus, epididymis, and intact didymus-epididymis tunicae. The blood culture executed for evening fever during antibiotic therapy has underlined an infection with Propionibacterium acnes. A following blood culture has shown an increase in Staphylococcus cohnii ssp. cohnii. Due to fever the patient has undergone left orchifunicolectomy with inguino-scrotal toilet. The anatomical pathological examination has also shown the presence of nonspecific granulomatous inflammation compatible with Propionibacterium acnes infection. Conclusion. The onset of an intrascrotal abscess likely sustained by Propionibacterium acnes complicated by a possible systemic Staphylococcus cohnii ssp. cohnii suprainfection is an exceptional event that, in our case, has been resolved with surgical toilet.